Van der Waals heterostructures of two-dimensional transition metal dichalcogenides for broadband and infrared photodetection - Ahmed Ramadan Abdelmontaleb Elbanna (Nanyang Technological University, 2024)
Two-dimensional (2D) materials have garnered significant attentions for their exceptional properties and potential applications in optoelectronics. Their unique electronic, optical, and mechanical characteristics have sparked immense interest in various technological domains, including photodetectors. The integration of different types of 2D materials and their combination with other materials and structures has resulted in hybrid systems that offer enhanced versatility and tunability. These hybrid systems enable the engineering of novel properties and functionalities that are unattainable in individual materials alone. Despite advancements in 2D-material-based photodetectors, certain limitations persist, necessitating further research. This thesis explores the potential of heterostructures of transition metal dichalcogenides (TMDs) for broadband and infrared (IR) photodetection. Conventional photodetectors are typically designed to detect light intensity within a specific wavelength range using a fixed detection mechanism. Developing a broadband and multi-functional detector controlled by multiple parameters would yield a versatile optoelectronic device with a broader range of applications. By engineering the band alignment in a SnSe2/MoS2 heterostructure, we have demonstrated a photodetector with high sensitivity, broadband response (266 nm to 1100 nm), and multi-mode operation (photoconductive and photovoltaic). It can also switch between positive and negative photoconductance based on multiple parameters such as wavelength, gate voltage, and laser power. The unique wavelength band-dependent photoconductance, exhibiting positive behavior in the ultraviolet and visible bands, coupled with negative behavior in the IR band, enables it to function as a day/night detector. The multifunctionality of our photodetector is attributed to carrier transport, interlayer exciton trapping at the SnSe2/MoS2 interface due to the large band offset, and the formation of a unilateral depletion region. This study provides insights into the ambipolar photoresponse in TMDs heterostructures and suggests promising directions for their application in photodetectors and multi-functional optoelectronic devices. The low absorption efficiency of individual 2D materials due to their thin nature necessitates innovative strategies to enhance light absorption and device efficiency. Overcoming this challenge requires approaches such as surface plasmon resonance, hybridization with 0D or 1D materials, heterostructure design, and integration with optical cavities. By leveraging the type II band alignment in TMDs heterostructures and employing cavity design, we achieved unprecedented photoresponse enhancement. The responsivity of the photodetector on the cavity surpassed that on the SiO2 substrate and previously reported 2D-material-based cavity photodetectors. This research provides valuable insights into the potential use of suitable 2D heterostructures with appropriate band alignment and cavity engineering for high-performance photodetection. Designing materials and devices for the mid-wave (MW) to long-wave (LW) IR range presents a challenge. Narrow bandgap semiconductors like HgCdTe, GaSb/InAs, InSb, and SiAs have dominated the commercial market in this range. However, their finite exciton binding energies, lower than thermal energy at room temperature, require cryogenic cooling, complicating device architectures besides the lattice matching requirement and expensive crystal growth processes. The absence of dangling bonds in 2D materials allows the stacking of different materials on various substrates without lattice matching constraints. Moreover, their high excitonic binding energies enable the demonstration of highly sensitive photodetectors operated at room temperature. However, suitable 2D material candidates for IR photodetection are limited. In this context, we demonstrated LWIR photodetection in TMDs heterostructures by harnessing the interlayer excitons, extending the photoresponse of the parent materials from the visible and near-infrared (VIS to NIR). These findings underscore the potential of controlling the band alignment in TMDs heterostructures as an efficient strategy to enable new opportunities for long-wavelength detection and sensing in cases where suitable 2D materials with appropriate bandgaps are lacking. Lastly, a comprehensive summary and conclusions are provided, highlighting the key findings and outcomes. Additionally, the potential future breakthroughs on the horizon are discussed, shedding light on promising avenues for further research and development. Overall, this thesis provides valuable insights into the potential application of 2D materials and their heterostructures in optoelectronic devices, offering promising directions for advancing photodetection technologies and multi-functional optoelectronic devices.